Brazilian Archisotoma Linnaniemi (Collembola, Isotomidae), with description of a new species from an oceanic atoll - de Lima, Estevam C. Araujo; Zeppelini, Douglas; de Mendonça, Maria Cleide (Zootaxa, 2019)
We summarize the distribution and habitat of Brazilian Archisotoma species, a taxonomic key for all species of the genus is given and a new species is described from intertidal sand of the Biologial Reserve Atol das Rocas, Brazil. Archisotoma jariani sp. nov. belongs to the besselsi group, recognized by small size, tibiotarsus III with stiff outer spur, maxillary head with thin simple capitulum, 3–2 pairs of trichobothria on abdominal segment VI. This is the first species of Collembola recorded from Atol das Rocas.